Transdiaphragmatic approaching in deceased donor liver transplantation for Budd-Chiari Syndrome: Surgical challenge – Case report - Fonseca Neto, Olival Cirilo Lucena da (2019)
Introduction: Budd-Chiari is a heterogeneous syndrome of non-specific etiology, characterized by obstruction of hepatic venous outflow at the level of the hepatic veins, up to the right atrium. In those patients, fibrosis of unknown etiology is frequently found between diaphragm and suprahepatic vena cava, making dissection and anastomoses unfeasible in this segment. Purpose: To report and review surgical technique challenges regarding the transdiaphragmatic approach and cavoatrial anastomosis in liver transplantation due to complete occlusion of the retrohepatic inferior vena cava. Method: Case report based on surgical observations, clinical records and images produced during follow-up of the patient in the transplantation service. Data from literature on Pubmed platform supported the discussion. Conclusions: Transdiaphragmatic approach and cavoatrial anastomosis are shown as a feasible alternative in current literature for Budd-Chiari syndrome patients needing transplantation. Replacement of the infrahepatic vena cava depends on development of collaterals through the azygous system and must be assessed during the preoperative period.